(untitled) (Bangladesh Journal of Anatomy, 2009)
Context: Vermiform appendix is an organ with immunological function in the abdominal cavity which is variable in position and length. It is important in different disease processes, such as appendicitis, carcinoma and diverticulitis. Appendicitis is the most important clinical condition. Appropriate anatomical knowledge about vermiform appendix is important for surgeons, pathologists and other physicians for proper diagnosis and management of appendicitis and carcinoma. Study design: Descriptive type of study. Place and period of study: Department of Anatomy, Sir Salimullah Medical College Hospital, Dhaka, from January 2006 to June 2007. Materials and methods: Sixty (60) human postmortem vermiform appendix, age ranging from 0 to 65 years. Samples were observed in situ in the unclaimed dead bodies within 24 hours of death. Results: Retrocaecal position was highest (65%) followed by pelvic (31.7%) and post ileal (3.3%). Subcaecal and pre ileal varieties were not found. Conclusion: To establish a data for Bangladeshi people, future studies are necessary by using larger sample size from different age and sex groups. To determine position of vermiform appendix, sonological studies are also recommended. Key words: position, vermiform appendix doi: 10.3329/bja.v7i1.3015 Bangladesh Journal of Anatomy January 2009, Vol. 7 No. 1 pp. 34-36